Un análisis de las dificultades en la formación de iniciativas legislativas en favor de los pueblos indígenas en el Perú (2016-2019) - Aguirre Rodríguez, Yeimis Dayanne (2024)
The thesis addresses the problem of the legislative representation of indigenous communities in the Peruvian political context, highlighting the lack of state support for indigenous governance and their recognition as political subjects. The research proposes to analyze how indigenous parliamentarians have developed a representative discourse and faced challenges in its execution, with the aim of providing strategies for genuine multicultural consolidation. A qualitative approach is used, operationalizing "parliamentary performance" by systematizing key indicators, such as the number of proposed legislative initiatives, their approval and publication, and relevance to indigenous issues. The methodology focuses on interviews, analysis of laws, official State documents and journalistic reports, from which clarifying perspectives of the problem and the context in which it develops are obtained. The selection of indigenous representatives is based on criteria such as self-identification, community participation, experience in indigenous issues and community support. The thesis seeks to understand the contribution of indigenous representation in the formulation of laws, highlighting its influence on the legislative process.